STRATEGI GURU AQIDAH AKHLAK DALAM MENANAMKAN AKHLAKUL KARIMAH DI MADRASAH ALIYAH SALAFIYAH SYAFI’IYAH TEBUIRENG JOMBANG - Romadhon, Achmad Ainur; Burhanuddin Ridlwan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigates the strategies employed by Aqidah Akhlak teachers in instilling akhlakul karimah (noble character) among students at Madrasah Aliyah Salafiyah Syafi’iyah Tebuireng Jombang. The research departs from a critical gap between the idealized objectives of Islamic education, which place character formation at its very core, and observable classroom realities where students conduct frequently falls short of akhlakul karimah standards. The study aims to describe the teachers' strategies, identify supporting and inhibiting factors, and analyze outcomes of strategy implementation on students' moral development. A qualitative approach with a case study design was employed, with data gathered through non-participant observation, in-depth interviews with the school principal, Aqidah Akhlak teachers, and students, and documentation review. Data analysis followed the Miles and Huberman interactive model (data reduction, data display, and conclusion drawing), while data validity was ensured through source and method triangulation. Results reveal that Aqidah Akhlak teachers implement three interlocking strategies: exemplary conduct (keteladanan), habituated practice (pembiasaan), and moral value integration within the learning process. Rather than operating separately, these strategies reinforce one another in addressing the cognitive, affective, and psychomotor dimensions of character formation simultaneously. Supporting factors include the madrasah's religious environment, institutional policies and programs, teacher commitment, and parental collaboration; inhibiting factors encompass student background heterogeneity, external social influences, limited instructional time, and insufficient parental supervision at home. The study concludes that consistently and synergistically applied strategies yield sustained internalization of akhlakul karimah, effectively bridging the gap between moral knowledge and lived character.